DETEKSI DINI KETERLAMBATAN TUMBUH KEMBANG ANAK DENGAN MEDIA DENVER - Eliyana Lulianthy; Dwi Khalisa Putri; Khulul Azmi; Rafhana Meidina; Dewi Sartika; Rega Fransiska (Politeknik 'Aisyiyah Pontianak, 2023)
The Central Bureau of Statistics (BPS) (2023) states that the population of Indonesia in 2022 will be 275 million people, and 8% (22 million people) of this figure consist of children aged less than 5 years. The child population as the nation's next generation will continue to grow. Therefore, large investments are needed in the fields of health, education and child welfare. The aim of this activity is to carry out early detection of delays in children's growth and development in Sungai Kunyit Hulu Village, Sungai Kunyit District, Mempawah Regency. The method for implementing this community service activity is Child Growth and Development Examination using Denver. The target achievement in this activity is to get an overview of the conditions of child growth and development in Sungai Kunyit Hulu Village, so that a follow-up plan can be determined to overcome this problem. The results of examining children's growth and development using Denver showed that 50% of children experienced suspected growth and development delays and 9% of children could not be tested because the children refused to take the test during the examination. The obstacle to this activity is that the posyandu room is not conducive, so the child does not have freedom during the growth and development examination. Conclusion: The results of the examinations that have been carried out indicate that some children experience suspected delays in growth and development. The participation of parents and cadres as well as village midwives is needed to routinely carry out promotive and preventive activities to improve children's health